(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
This study examines cultural events as catalysts for tourist destinations at Bujora Cultural Site, Magu District located at Mwanza region in Tanzania, using TALC theory to frame development and sustainability. It investigated how events affect tourist perceptions and satisfaction, their role in promoting and preserving local culture. This study employed a mixed-methods approach. The sample included 44 participants—tourists, local business owners, and staff—selected. Data were collected through survey questionnaires and interviews. SPSS and Thematic analysis were used as data analysis tools. Findings indicate that cultural events have overwhelmingly positive impacts on tourist dentations. A substantial majority of tourists reported favourable perceptions, with events enhancing satisfaction and overall experience. The events emerged as crucial for cultural preservation, fostering community pride and mutual understanding among locals and visitors. Economically, 90% of local businesses noted increased tourist spending during events. Both tourists and businesses concurred that cultural events strengthen the site’s competitiveness. The study concludes that cultural events effectively catalyze tourism development at Bujora cultural site. It recommends collaboration among site management, local government, and community stakeholders to improve infrastructure, marketing, quality assurance, and sustainable community involvement, aiming to maximize economic benefits while preserving culture.